Pengaruh Pelaksanaan Internal Audit ISM Code Terhadap Operasional Kapal MV. Martha Golden pada PT. Multi Jaya Samudera Belawan - Hida Elma Kristina Malau; Dafid Ginting; Yusnidah Yusnidah (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This research aims to analyze the impact of implementing the International Safety Management (ISM) Code internal audit on the operational smoothness of the vessel MV. Martha Golden, managed by PT. Multi Jaya Samudera Belawan. The implementation of the ISM Code is a mandatory requirement regulated by Law No. 17 of 2008 concerning Shipping, designed to ensure safe ship operation and the prevention of marine pollution. The research methodology employed is field research (field research) through observation and the collection of direct operational data, complemented by a literature review (library research) to examine related regulations and theory. The findings demonstrate that the consistent execution of the ISM Code internal audit has a significant positive influence on improving the vessel's safety and operational integrity. This audit, carried out by the Designated Person Ashore (DPA), encompasses scheduling, conducting thorough inspections onboard, and reporting findings. Consistent auditing minimizes the risk of accidents at sea, enhances the compliance of all crew members with the applicable Safety Management Sistem (SMS), and ensures that the vessel operates safely and efficiently according to international standards. The study concludes that discipline in performing internal audits and the crew's adherence to SMS procedures are the primary keys to maintaining operational integrity. It is recommended that the company increase the frequency and quality of internal audits and crew training to ensure the vessel's safety and operational efficiency are consistently maintained.